Benin : Second Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2007)
The Second Poverty Reduction Strategy Paper (SCRP) for Benin explains growth strategy for poverty reduction. The SCRP emphasizes the importance of addressing governance, transparency, and corruption. Capacity for budget management will also have to be improved at the level of sectoral ministries. The SCRP could be strengthened in future progress reports. To facilitate the achievement of key objectives, the authorities should establish appropriate institutions that implement, monitor, and evaluate progress under the strategy.